2016
DOI: 10.1117/1.jmi.3.4.043503
|View full text |Cite
|
Sign up to set email alerts
|

Noise performance of low-dose CT: comparison between an energy integrating detector and a photon counting detector using a whole-body research photon counting CT scanner

Abstract: Photon counting detector (PCD)-based computed tomography (CT) is an emerging imaging technique. Compared to conventional energy integrating detector (EID)-based CT, PCD-CT is able to exclude electronic noise that may severely impair image quality at low photon counts. This work focused on comparing the noise performance at low doses between the PCD and EID subsystems of a whole-body research PCD-CT scanner, both qualitatively and quantitatively. An anthropomorphic thorax phantom was scanned, and images of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 11 publications
(21 reference statements)
0
67
0
1
Order By: Relevance
“…Several studies have shown that the PCD‐CT have various advantages compared to the conventional EID‐CT, including improved iodine contrast, reduced electronic noise, more stable CT number in low dose realm, and dose‐efficient high‐resolution capability . The DS‐PCD system is expected to preserve these advantages as it is equipped with the same core PCD technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the PCD‐CT have various advantages compared to the conventional EID‐CT, including improved iodine contrast, reduced electronic noise, more stable CT number in low dose realm, and dose‐efficient high‐resolution capability . The DS‐PCD system is expected to preserve these advantages as it is equipped with the same core PCD technology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the PCD-CT have various advantages compared to the conventional EID-CT, including improved iodine contrast, reduced electronic noise, more stable CT number in low dose realm, and dose-efficient highresolution capability. [6][7][8][9][10] The DS-PCD system is expected to preserve these advantages as it is equipped with the same core PCD technology. These advantages can potentially be used to improve image quality under the same radiation dose, or to reduce patient dose while maintain the same image quality such as resolution and noise level.…”
Section: Discussionmentioning
confidence: 99%
“…PCDs measure individual photons and their associated energy, rather than the integrated charges generated by all measured photons, as occurs with an energy-integrating detector (EID). This provides unique benefits compared to EIDs, including lower electronic noise, higher contrast to noise ratio (CNR) and improved dose efficiency, as demonstrated in recent studies (Schmidt, 2010, Gutjahr et al, 2016, Yu et al, 2016b). In addition, the energy discrimination nature of the PCD enables a simultaneous multi-energy imaging technique using a single tube, single tube potential (kV), and single detector (Roessl and Proksa, 2007, Schlomka et al, 2008, Kappler et al, 2014, Li et al, 2015, Faby et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CdTe is a II-VI compound semiconductor material, with attractive properties for a number of energy 1 and imaging applications. 2 These properties include a direct bandgap in the infrared region (1.5 eV), and a relatively high density of 5.85 g/cm 3 (which confers enhanced stopping power for high energy radiation).…”
mentioning
confidence: 99%
“…2 At present, CdTe is being intensively researched as a direct detector material for tomographic medical imaging, 3 but to date it has not seen mainstream application. 2 Growth of CdTe single crystals is a difficult and expensive process, and present devices are affected by relatively high defect densities and performance instability.…”
mentioning
confidence: 99%